Pathophysiological substantiation of the effectiveness of quercetine use in coronavirus disease (COVID-19) therapy - I. A. Zupanets; S. K. Shebeko; N. P. Bezugla; I. A. Otrishko (Zaporozhye State Medical University, 2020)
In the absence of effective and safety therapy for COVID-19 patients, today the search for new methods of treatment is the most actual topic in medicine and pharmacy. High mortality (7.1 %) due to the development of acute respiratory distress-syndrome, which is caused by cytokine storm, dictate the need to develop a new approaches to the influence on a various pathogenetic links of the disease in the complex therapy of such patients. This review summarizes the data of experimental and clinical studies of the pharmacological properties of quercetin (mechanisms of action, pharmacological effects) and quercetin-containing drugs Quertin and Corvitin (oral and parenteral dosage forms), which are presented on the pharmaceutical market of Ukraine. The results of numerous studies indicate that quercetin has (among others) high anti-inflammatory, antiviral, membrane-stabilizing, immunomodulating and antioxidant effects. The mechanisms for the realization of these pharmacological effects are well studied and make it possible to use quercetin as a pathogenetic therapy (effect on the various pathogenesis links) in patients with coronavirus infection. This dictates the need for the conducting of appropriate clinical trials of these drugs for the prevention and treatment of coronary infection. Clinical trials results may be an innovative strategy in the treatment of COVID-19 patients.